Mechanical properties-morphology corroboration of spheroidized AISI1040 steel. (14th June 2019) - Harisha, S R; Sharma, Sathyashankara; Kini, U Achutha; Sharma, Aniruddh; Joshi, Neel
Abstract: Medium carbon steels have importance in production due to their tendency to get the required property for suitable application. Heat treatment, especially spheroidization annealing not only softens the lattice but also spheroidizes the eutectoid carbides. The size of these discrete spheroids may play an essential role in improving machining characteristics and hence the machinability. The work is mainly devoted to correlate the heat treatment (spheroidization) with mechanical characteristics. The microstructure shows partial spheroidization in all the heat treatment conditions with a considerable decrease in hardness and strength with increase in spheroidization duration.